Institutional analysys of the image of the Secretaria de Relaciones Exteriores of Mexico and external communication with the migrant population segment - Gadea-Aldave, Gilda (Universidad Autónoma de Tamaulipas, 2011)
This article aims to present some of the results of a larger investigation that has focused entirely on the study of external communication of the Ministry of Foreign Affairs (SRE). To do this, between 2008 and 2010, there has been a communication audit that included communication performance analysis and operation of the central delegation of the SRE in Mexico City, its website (http://www.sre. gob.mx /) and brochures for distribution (in this specifi c case of Mexican migrant Guide, published and disseminated by the Ministry of Foreign Affairs, 2004), in order to meet the projected image of the institution to its public. Additionally, among numerous other factors, the investigation established to study a specific audience segment: the Mexican migrant population to the United States of America, in order to determine what degree of influence, if any, that institution has in this population segment through promoting or encouraging migration.